Aluminum borate whisker-based lattices with a hierarchical pore structure obtained via digital light processing. Issue 16 (15th August 2022) - Liu, Xinger; Dong, Xue; Li, Xin; Li, Lan; Yan, Liwen; Liu, Jiachen; Guo, Anran
Abstract: To satisfy the ever-increasing demand for aluminum borate porous ceramics with complex shapes and tunable pore structures in a diverse set of fields, aluminum borate whisker-based lattices with hierarchical pore structures were fabricated by a combination of in situ reaction and digital light processing three-dimensional (3D) printing. The optimal dispersant concentration and exposure parameters for 3D printing were determined based on analyses of the rheological properties and working curves of the Al2 O3 –B2 O3 photosensitive slurries. The effects of the B2 O3 /Al2 O3 molar ratio on the morphology and properties of aluminum borate lattices were investigated. The results showed that the addition of an excess of B2 O3 was beneficial to the growth of aluminum borate whiskers. When the B2 O3 /Al2 O3 molar ratio was set to 6:9, the resultant aluminum borate lattices exhibited a typical hierarchical pore structure, including inherent large pores in the lattices and small pores formed by interlocked aluminum borate whiskers generated in situ within the struts. This unique hierarchical pore structure endowed the ceramic lattices with a high compressive strength (1.18 MPa) and porosity (82.58%), as well as non-brittle fracture characteristics. Owing to these outstanding properties, aluminum borate whisker-based lattices are promising candidates for high-temperature thermal insulation, catalyst supports, acoustic absorption, and particle filtration.